On the type species of the genus Aetius O. Pickard-Cambridge, 1896: The first description of male with notes on cymbial notch and mating plug (Araneae: Corinnidae: Castianeirinae) - Sudhin, Puthoor Pattammal; Nafin, Karunnappilli Shamsudheen; Simmons, Zoë; Sudhikumar, Ambalaparambil Vasu (Zootaxa, 2016)
The rare ant mimicking sac spider genus Aetius was erected by O. Pickard-Cambridge in 1896 based on an unspecified number of female specimen(s) collected from Sri Lanka. The type species of the genus, A. decollatus O. Pickard-Cambridge, 1896, has been redescribed twice based on the holotype (Majumder & Tikader 1991; Deeleman-Reinhold 2001). Reimoser (1934) recorded the genus for the first time from India, who collected a male specimen from Mudumalai Tiger Reserve in Tamil Nadu State of southern India. This specimen was identified as A. decollatus, but it was never formally described and was later recognised to be a penultimate male (Dankittipakul & Singtripop 2013). Deeleman-Reinhold (2001) described the second representative of the genus, A. nocturnus, based on a single female specimen from Borneo, 105 years after the establishment of the genus. Dankittipakul & Singtripop (2013) described the male of A. nocturnus, thereby revealing the male genitalia of the genus, but the type species was still known only from the female sex.